ANALISIS PERILAKU SOSIAL SECOND BRANDED MASYARAKAT KOTA TIMIKA - Stepanus Sandy; Riana Riana; Winda Oratmangun (Jurnal Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the determining factors of second branded behavior of the people of Timika city. The data collection techniques used to obtain data in this research are observation techniques and questionnaires. The analysis used in this research is confirmatory factor analysis. The results obtained from the analysis in this research are that two new factors were formed from several indicators that have been identified, namely the brand intelligence factor and the celebrity intelligence factor which are the determining factors for the second branded social behavior of the people of Timika city.